Efektivitas Model Pembelajaran Savi (Somatis Auditori Visual) terhadap Kemampuan Berpikir Kritis Siswa Kelas VI Mata Pelajaran IPA di MI NW Bagik Nyala - Izzuddin, Ahmad (MASALIQ, 2022)
This study aims to determine the effectiveness of using the SAVI Learning Model (Somatic Auditory Visual) learning model for the critical thinking skills of class VI students at MI NW Bagik Nyala in the 2021/2022 Academic Year. Data collection techniques using observation techniques and tests in the form of essays. Observation data on the implementation of learning reached 75% for the experimental class with good criteria and test scores were in the range of 75.005 < K with a very critical thinking category. While the control class is 58.33% with fairly good criteria and test scores are in the range of scores 58.335 < K < 75.005 with the category of critical thinking. Hypothesis testing using the t test and obtained t count = 10.80 and t table 1.6788 with dk 48 and a significant level of 5% so that the null hypothesis is rejected and the alternative hypothesis is accepted. So it can be concluded that it can significantly increase the effectiveness of the SAVI Learning Model (Somatic Auditory Visual) learning model on students' critical thinking skills.